Candidate New Rotavirus Species in Sheltered Dogs, Hungary - Mihalov-Kovács, Eszter; Gellért, Ákos; Marton, Szilvia; Farkas, Szilvia L.; Fehér, Enikő; Oldal, Miklós; Jakab, Ferenc; Martella, Vito; Bányai, Krisztián (Emerging infectious diseases, 2015)
We identified unusual rotavirus strains in fecal specimens from sheltered dogs in Hungary by viral metagenomics. The novel rotavirus species displayed limited genome sequence homology to representatives of the 8 rotavirus species, A-H, and qualifies as a candidate new rotavirus species that we tentatively named Rotavirus I.